Dampak Beban Kerja Terhadap Intensi Turn Over Pada Karyawan - Monika Audiva Pane; Oktariani Oktariani (Pusat Riset dan Inovasi Nasional, 2023)
Every company definitely wants good and adequate quality human resources, with the existence of quality human resources makes the company able to compete with other companies. According to Firdaus (Putra et al., n.d.). Therefore the welfare of employees is also very important to note.Especially in giving workload to employees. Each work unit has a different workload. A workload that is too high can cause an employee to become stressed, not to mention the job demands given by the company so that its employees give the best results. Each individual has different resilience to the workload and responsibilities given, the higher the workload given, the higher the stress level that will be experienced by the individual, conversely the lower the workload given, the lower the stress level. A high workload can make employees decide to quit or leave the company and look for a better company. This situation is also known as intensive turnover. In the case of Indonesia, the phenomenon of turnover intention is well recognized by both academics and practitioners. Every year there are around 10-12% of employees who turn over.